2017
DOI: 10.1038/ncb3596
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial permeabilization engages NF-κB-dependent anti-tumour activity under caspase deficiency

Abstract: Apoptosis represents a key anti-cancer therapeutic effector mechanism. During apoptosis, mitochondrial outer membrane permeabilisation (MOMP) typically kills cells even in the absence of caspase activity. Caspase activity can also have a variety of unwanted consequences that include DNA-damage. We therefore investigated whether MOMP-induced caspase-independent cell death (CICD) might be a better way to kill cancer cells. We find that cells undergoing CICD display potent pro-inflammatory effects relative to apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
203
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(214 citation statements)
references
References 43 publications
9
203
1
1
Order By: Relevance
“…We next investigated an association between mitochondrial mtDNA release and activation of a STING‐dependent interferon response. For this purpose, we used SVEC 4–10 murine endothelial cells, which we have previously shown have an intact cGAS‐STING signalling pathway (Giampazolias et al , ). To induce rapid mitochondrial apoptosis, SVEC cells were treated with ABT‐737 together with the MCL‐1 inhibitor S63845 (Kotschy et al , ), and cell death was monitored by SYTOX Green uptake and IncuCyte live‐cell imaging (Fig A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next investigated an association between mitochondrial mtDNA release and activation of a STING‐dependent interferon response. For this purpose, we used SVEC 4–10 murine endothelial cells, which we have previously shown have an intact cGAS‐STING signalling pathway (Giampazolias et al , ). To induce rapid mitochondrial apoptosis, SVEC cells were treated with ABT‐737 together with the MCL‐1 inhibitor S63845 (Kotschy et al , ), and cell death was monitored by SYTOX Green uptake and IncuCyte live‐cell imaging (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial apoptosis is considered a non‐inflammatory form of cell death, allowing the host to quickly and efficiently clear away dead cell corpses without provoking an immune response (Arandjelovic & Ravichandran, ). Recently, others and ourselves have shown that caspase activity is essential for the non‐inflammatory nature of mitochondrial apoptosis; if caspase activity is blocked following MOMP, cell death still occurs, but a type I interferon (IFN) response and NF‐κB activation ensues (Rongvaux et al , ; White et al , ; Giampazolias et al , ). This leads to pro‐inflammatory cytokine production and an immune response towards the dying cell that can initiate anti‐tumour immunity (Giampazolias et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It will be interesting to test whether mtDNA release also takes place in these organisms, and whether there is a role for MOMP in inflammation in invertebrates. Irrespective of mtDNA release, caspase‐deficient MOMP can also induce TNF production via SMAC‐mediated downregulation of IAP proteins and activation of the NF‐κB pathway (Giampazolias et al , ). Thus, Bax and Bak emerge as key modulators of cell death‐associated inflammation.…”
Section: Kinetics Of Momp‐driven Inflammationmentioning
confidence: 99%